Management Views on Corporate Social Responsibility in Commercial Banks of Nepal (Socio-Economic Development Panorama, 2008)
Despite the growing interest in Corporate Social Responsibility (CSR), a shadow of doubt remains as to whether managers of various countries and industry sectors posses a high or low degree of positive strategic and moral view on CSR. In this context, this paper examines the managers' views on CSR in commercial banks of Nepal. For this, managers from different commercial banks were asked to give their opinion on a five-point scale regarding two propositions concerned with strategic and moral dimensions of CSR. The study finds that the view, which holds that CSR is a moral duty of companies bounded towards the society, is much stronger than the strategic view, which holds that CSR contributes to the financial success of the company in the long run. Another crucial finding is that the top level management of private sector commercial banks in particular assumes a win-win relationship between CSR and financial performance of the company. A couple of inferences can be drawn from these findings. Firstly, managers of commercial banks in Nepal are clearly aware of the company's moral duty towards different segments of the society. Second, today's managers of commercial banks in Nepal are quite convinced enough with the fact that CSR and profit seeking maximization acts are not conflicting goals of the firm. Keywords: corporate social responsibility, banking organizations, competitive advantage, positive motivation, moral duty, strategic views Socio Economic Development Panorama, Vol. 1, No.3(2008) pp. 119-130